2016
DOI: 10.1093/arclin/acw002
|View full text |Cite
|
Sign up to set email alerts
|

Normative Data of the Montreal Cognitive Assessment in the Greek Population and Parkinsonian Dementia

Abstract: The Montreal Cognitive Assessment (MoCA) is a brief cognitive instrument for the measurement of dementia. The aim of the present study is to provide normative data for the MoCA test in the Greek speaking population and to measure its validity in a clinical group of parkinsonian dementia participants. A total of 710 healthy Greek speaking participants and 19 parkinsonian dementia participants took part in the study. Both, the MoCA test and a neuropsychological test battery (digit span, semantic verbal fluency, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
53
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 28 publications
11
53
3
1
Order By: Relevance
“…Consistent with previous findings, older age was associated with lower scores [11][12][13][14][15][16][17][18][31][32][33][34][35]. We found a 1.0-point difference between the youngest (65-75) and oldest (75-85) groups; other studies have reported a difference of 0.6-2.4 points between similar age groups [13,[15][16][17]31].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with previous findings, older age was associated with lower scores [11][12][13][14][15][16][17][18][31][32][33][34][35]. We found a 1.0-point difference between the youngest (65-75) and oldest (75-85) groups; other studies have reported a difference of 0.6-2.4 points between similar age groups [13,[15][16][17]31].…”
Section: Discussionsupporting
confidence: 91%
“…Gender was significantly associated with MoCA score, with a mean for men of 0.45 points below the mean for women. This is consistent with a Greek normative study showing a difference in mean of 0.3 points between sexes [11]. In a study by Larouche et al, in which mean scores were not presented, male sex was also a negative predictive factor in their regression model [12].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Interestingly, MoCA scores were sometimes reported to be higher in healthy aging women than men. [23][24][25] The slower development of cognitive impairment in females may in part reflect their relative high baseline ability in the areas susceptible for Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%